STUDYING ASSOCIATIONS OF TWO COMMON S27P AND -15С→T POLYMORPHISMS OF THE INTERLEUKIN-3 GENE WITH DEVELOPMENT OF ALLERGIC AND NON-ALLERGIC BRONCHIAL ASTHMA IN RUSSIANS FROM THE CENTRAL-CHERNOZEM REGION - A. V. Polonikov; V. P. Ivanov; D. A. Belugin; I. V. Khoroshaya; M. A. Solodilova; V. I. Panfilov (Медицинская иммунология)
Abstract. The purpose of our study was to investigate whether S27P and -15С→T single nucleotide polymorphisms of the IL3 gene are associated with susceptibility to bronchial asthma (BA) in Russians living in the Central-Chernozem region of Russia. DNA samples obtained from 216 unrelated patients with BA and 214 healthy controls were typed for S27P and -15С→T polymorphisms in the IL3 gene by PCR-RFLP methods. Gender-based differences in the distribution of IL3 genotypes have been revealed between controls and patients with asthma. Both S27P and -15С→T polymorphisms were found to associate with common susceptibility to BA predominantly in females (p=0,05). Studied genetic variants of IL3 gene were in strong linkage disequilibrium with each other (p<0,0001). Further studies are required to investigate phenotypic expression of S27P and -15С→T polymorphisms of IL3 gene and to clarify their roles in the pathogenesis of bronchial asthma.